Meningkatkan Komitmen Kerja Guru: Analisis Peran Motivasi Intrinsik Dan Emotional Intelligence: Improving Teachers' Work Commitment: Analysis of the Role of Intrinsic Motivation and Emotional Intelligence - Mohzana Mohzana; Almira Ulimaz; Tuti Marjan Fuadi; Agus Rofi'i; Yohanis Hukubun; Aji Permana Putra (ITScience (Information Technology and Science), 2024)
Teachers’ work commitment is a key element that influences the quality of education in schools. Highly committed teachers tend to be more dedicated to their profession, resulting in better quality teaching and positive relationships with students. Intrinsic motivation is an interest that arises within a person, either in satisfaction or personal achievement, when carrying out a particular job. On the other hand, emotional intelligence refers to the teacher’s ability to recognize, understand, and handle their own emotions and the emotions of others, such as students. This study will explore intrinsic motivation and emotional intelligence to improve teachers’ work commitment. This study uses a quantitative approach, using a survey method involving 150 teachers. The questionnaire used in this data collection measured intrinsic motivation, emotional intelligence, and teachers’ work commitment. Multiple regression was used to analyze the collected data and identify the relationship between the three variables. The results showed that intrinsic motivation and emotional intelligence significantly positively influenced teachers’ work commitment. However, the impact of emotional intelligence proved to be much greater than intrinsic motivation. These findings indicate that developing emotional intelligence can be an effective way to improve teachers’ work commitment. Thus, this study suggests that schools should place more emphasis on emotional intelligence training in the context of teacher professional development.